Discordant Grading of Aortic Stenosis Severity: New Insights from an In Vitro Study. Issue 5 (3rd September 2019) - Adda, Jérôme; Stanova, Viktoria; Zenses, Anne-Sophie; Clavel, Marie-Annick; Barragan, Paul; Penaranda, Guillaume; Habib, Gilbert; Pibarot, Philippe; Rieu, Régis
ABSTRACT: Background : Low gradient (mean gradient, < 40 mmHg) aortic stenosis (AS) may occur in conjunction with a small valve effective orifice area (EOA) < 1 cm 2 . This discordant grading in AS severity raises challenges from both a diagnostic and therapeutic standpoint. We sought to identify echocardiographic markers of severe AS in normal and low flow conditions in vitro . Methods : In an in vitro mock circulatory system, we tested 6 degrees of AS severity (3 severe and 3 nonsevere), and 3 levels of stroke volume (30, 50, 70 ml), heart rate (60, 80, 100 bpm), and mean arterial pressure (100, 120, 140 mmHg). MG and EOA were measured by Doppler-echocardiography. Results : In normal flow conditions, a MG of 40 mmHg corresponded to an EOA of 0.85 cm 2, and an EOA of 1.0 cm 2 to a MG of 28 mmHg. The presence of EOA < 0.85 cm 2 and MG between 24 and 40 mmHg in the low-flow condition yielded a 100% specificity for severe AS. In normal flow conditions, these thresholds were respectively < 0.9 cm 2 and > 36 mmHg. Conclusion : Low gradient AS may occur in severe AS in both low and normal flow conditions. The presence of a valve EOA < 0.85 cm 2 with an MG ≥ 25 mmHg may be used as a criteria to confirm severe AS in presence of low flow. In patients with normal-flow, a MG ≥ 37 mmHg is generally suggestive of severe AS. Abbreviations : AS: aortic stenosis; EOA: effective orifice area; HR: heart rate; LFLG: low-flow low-gradient; LVEF: left ventricular ejection fraction; MAP: mean arterial pressure; MG: mean gradient; NFLG: normal-flow low-gradient; SV: stroke volume